Kampanye Pertolongan pada Kecelakaan Pesawat dan Keamanan Penerbangan bagi Siswa SMA/SMK - Perangin Angin, Andi Frianto; Arta, Deddy Novie Citra; Biringkanae, Pipa; Kona, Musri; Bunahri, Rifqi Raza (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Fulfillment of safety requirements in the use of aircraft, airspace, flight navigation, airports, air transportation and other supporting facilities is known as aviation safety. Aviation security and safety must be a top priority for all parts of aviation service providers, especially airports, during their operations. So that flight operations are not disrupted by aviation accidents, such as aircraft failure during landing or take-off, and fires, they must be handled immediately. One part of dealing with emergencies at airports is aviation accident assistance and firefighting. This research uses a literature review method, namely by conducting a literature review or literature review. In order to get results. In a plane accident, an institution or team is definitely needed to help the accident victims, so a search and rescue or what in Indonesian is called search and rescue, was formed. Aviation security at an airport is the responsibility of the Airport Authority. Apart from forming an airport security committee, the Airport Authority also forms aviation security personnel at each airport it manages. The campaign discussing aid in plane crashes and aviation safety at high schools in Jayapura is very useful, this is because the knowledge they gain about aid in plane crashes while working in the aviation industry will produce high quality human resources.